Design, development and construction of a monitoring table tennis net - Gastinger, R.; Litzenberger, S.; Sabo, A. (Procedia Engineering, 2011)
This study's objective was to design, develop and construct a monitoring table tennis net to minimize mistakes in adjusting the net and achieve a constant and highly precise net height, net tension as well as detection of ball-net contacts during service (so called: let). Furthermore, it should improve and expand the standards for net adjustment which are unclear and not exactly reproducible at the moment. The monitoring device consists of a grey consoling housing, a custom-made force sensor, an electronic circuit, two graphical user interfaces, two height sensors, a let sensor, an electronic circuit and two graphical user interfaces. The proposed device provides a way for measuring net height and tension to ensure similar playing conditions (worldwide) and can be used for the detection of ball-net impacts during service.